DEVELOPING INTERACTIVE FUNDAMENTAL CHEMISTRY MULTIMEDIA IN GROWING GENERIC SKILL FOR TEACHER TRAINING STUDENTS - Khaeruman Khaeruman; Hulyadi Hulyadi (Universitas Pendidikan Mandalika Mataram, 2016)
Chemistry investigates interactions and reactions of particles as atom, ion, molecule, and their tendencies. Interactions occurred are so abstract that make them become difficult to be observed and documented. This becomes a problem in learning chemistry. It happens due to the separation of macroscopic and microscopic concepts. In fact, to be able to obtain the concept of chemistry as whole requires learning model which can integrate three aspects namely macroscopic, symbolic-conducted through practicum, and microscopic-conducted through modeling interactive media. This study aimed to developed interactive learning media for fundamental chemistry class. This study belongs to Educational Research and Development. In general, there were three steps conducted by the researcher namely analyzing, designing, and developing. Data obtained from this study was in the form of qualitative data consisted of suggestions and responses in likert scale. Validations result in interactive multimedia appearance showed that the average 85 was obtained-this was indicated as very good, in materials appropriateness the average 84 was obtained-this was indicated as good, and in programming appropriateness the average 85 was obtained-this was indicated as very good. The result in small group showed that interactive multimedia development was categorized as very good. This proven by the percentage appropriateness was 93.14%. Further, the researcher hopes that the product of this study can be useful in improving interest, motivation, and concept understanding of chemistry teacher training students so that they can relate learning material to real world in order to conduct meaningful learning.